590 VARIATION IN RECEIPT OF THERAPY AND SURVIVAL WITH PROVIDER-VOLUME IN NON-CURATIVE ESOPHAGO-GASTRIC CANCER: A POPULATION-BASED ANALYSIS. (17th September 2021) - Hallet, Julie; Davis, Laura; Mahar, Alyson; Lui, Ying; Zuk, Victoria; Gupta, Vaibhav; Earle, Craig; Coburn, Natalie
Abstract: : While surgical care by high-volume providers for esophago-gastric cancer (EGC) yields better outcomes, volume-outcome relationships are unknown for systemic therapy. We examined receipt of therapy and outcomes in the non-curative management of EGC based on medical oncology provider-volume. Methods: We conducted a population based retrospective cohort study of non-curative EGC over 2005–2017 by linking administrative healthcare datasets. The volume of new EGC consultations per medical oncology provider per year was calculated and divided into quintiles. High-volume (HV) providers were defined as the 4-5th quintiles. Outcomes were receipt of chemotherapy and overall survival (OS). Multivariate logistic and Cox-proportional hazards regressions examined the association between management by HV provider, receipt of systemic therapy, and OS. Results: 7, 011 EGC patients with non-curative management consulted with medical oncology. One-year OS was superior for HV providers (>11 patients/year), with 28.4% (95%CI: 26.7–30.2%) compared to 25.1% (95%CI: 23.8–26.3%) for low-volume (p < 0.001). After adjusting for age, sex, comorbidity burden, rurality, income quintile, and diagnosis year, HV provider was independently associated with higher odds of receiving chemotherapy (OR 1.13, 95%CI 1.01–1.26), and independently associated with superior OS (HR 0.89, 95%CI 0.84–0.93). Conclusion: Medical oncology provider-volume was associated with variation in non-curative management and outcomes of EGC. Care by a HV provider was independently associated with higher odds of receiving chemotherapy and superior OS, after adjusting for case-mix. This information is important to inform disease care pathways and care organization; increase in the number of HV providers may reduce variation and improve outcomes.